A splice site mutation c.1251G>A of ISPD gene is a common cause of congenital muscular dystrophy in Chinese patients. Issue 5 (7th January 2020) - Song, Danyu; Fu, Xiaona; Ge, Lin; Chang, Xingzhi; Wei, Cuijie; Liu, Jieyu; Yang, Haipo; Qu, Suqing; Bao, Xinhua; Toda, Tatsushi; Wu, Xiru; Xiong, Hui
Abstract : The predicted synonymous mutation c.1251G>A of ISPD (NM_001101426.3) is a hot spot causing exon 9 skipping in five patients.